Pelatihan Penanganan Telur Itik Asin Dengan Metode Pengasapan Di Desa Tonrong Kecamatan Baranti Kabupaten Sidenreng Rappang - Iranita Haryono (Pusat Riset dan Inovasi Nasional, 2023)
Tonrong Village is one of the villages in the Baranti District,Sidenreng Rappang Regency, South Sulawesi Province. There are several duck/duck breeders and business groups of boiled salted eggs which are produced traditionally with not too large a production amount, due to limited marketing caused by the many similar industries, both in the same village and sub-district, even in almost every sub-district there are also people who production of boiled salted eggs. Inspired by the smoked salted eggs of Brebes, the team took the initiative to make a smoking furnace/tool ​​to produce Tonrong smoked salted eggs, through Community Service activities. The smoking process can be done on salted eggs that have been boiled or steamed, of course with different results. The smoking process is carried out in the following settings: steamed salted eggs, processed for 30 minutes of steaming at a temperature between 70-75oC for maximum results. The result is for steamed eggs, perfectly cooked eggs, especially seen from the appearance of the egg yolks, but contain water so it is a bit soft while for eggs treated with smoking, salted eggs have an attractive color, a distinctive smell and very little water content so that the shelf life is more durable. compared to salted eggs that are steamed or boiled.